2022
DOI: 10.5603/demj.a2022.0039
|View full text |Cite
|
Sign up to set email alerts
|

Association between D-dimer and mortality in COVID-19 patients: a single center study from a Turkish hospital

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In some cases, thrombosis was found in asymptomatic forms of the disease [ 18 , 19 , 20 ]. In pediatric multisystem inflammatory syndrome, the laboratory findings suggest a procoagulant status with prominent increase of the D-dimer level, similar to patients with cytokine storm in acute COVID-19 infections [ 19 , 20 , 21 ]. Venous thrombosis is predominantly described, while reports of arterial thrombosis in children with COVID-19 are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, thrombosis was found in asymptomatic forms of the disease [ 18 , 19 , 20 ]. In pediatric multisystem inflammatory syndrome, the laboratory findings suggest a procoagulant status with prominent increase of the D-dimer level, similar to patients with cytokine storm in acute COVID-19 infections [ 19 , 20 , 21 ]. Venous thrombosis is predominantly described, while reports of arterial thrombosis in children with COVID-19 are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Kilic and Dalkilinc Hokenek indicate that patients with high D-dimer levels had higher in-hospital mortality rates. It is worth emphasizing here that [1] Zhang et al [6] showed that D-dimer levels larger than 2.0 g/mL on admission (a fourfold rise) might successfully predict in-hospital mortality in COVID-19 patients, indicating that D-dimer could be an early and useful marker to enhance COVID-19 patient care.…”
mentioning
confidence: 86%
“…To the Editor, we read with great interest the article by Kilic and Dalkilinc Hokenek concerning to association between D-dimer levels and COVID-19 patients' mortality [1]. Since December 2019, a new coronavirus known as SARS-CoV-2 has produced a global outbreak of respiratory sickness known as coronavirus disease 2019 (COVID-19), which is still spreading rapidly.…”
mentioning
confidence: 99%
“…It is well known that lymphocytes play a role in the infectious process. Furthermore, thrombocytes play an important role in the regulation of a number of inflammatory processes [13,14]. Changes in white blood cells, lymphocyte, and platelet counts are strongly associated with COVID-19 pneumonia [15].…”
Section: Introductionmentioning
confidence: 99%